Characteristics of Polish Business Aviation Services Market - Górnik, Karolina (Charakterystyka rynku usług transportu lotniczego dla biznesu w Polsce, 2010)
General characteristics and development trends of Polish business aviation services market are presented in the article. The analysis presented in this paper shows rapid development of these services in Poland in the foreseeable future, stimulated by Poland's accession to the EU structures and the prospect of 2012 UEFA European Football Championship co-hosted by the Ukraine and Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 53-61
Keywords: Polish business aviation services market; civil aviation services in the context of 2012 UEFA European Football Championship